Теплообмін та аеродинаміка біля вертикальної конічної труби на майданчику ТЕС - Чиркова, Анна Петрівна; Халатов, Артем Артемович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Розглянуто особливості теплообміну та аеродинаміки біля вертикальної конічної труби на майданчику ТЕС. Дослідження виконували в програмному пакеті ANSYS 2020-R1. У роботі застосовувався метод комп'ютерного моделювання 3D-моделі інфраструктури ТЕС. При комп'ютерному моделюванні використана RNG k– модель турбулентності. Проведені дослідження показують значний вплив розташування будівлі машинного залу на аеродинаміку димової труби та залежності від напрямку вітру.

The funnel is the most important element of the thermal power station. An appropriate arrangement of the system for the removal of the gaseous products of fuel combustion inside the funnel results in no moisture condensation and proper maintenance of the operation conditions of the funnel. To measure the temperature of combustion products along the funnel height we need to define the boundary conditions of the third kind for the external surface of the funnel. The studies showed that in the case of the uniform velocity profile, the heat exchange and aerodynamics on the surface of the single vertically arranged funnel have specific features conditioned by the funnel configuration and the contact of its base with the ground surface. In particular, the rear part of the funnel is characterized by a periodic change in the static pressure, velocity and the height heat loss coefficient. The purpose of this research was to define the average heat loss along the height of the conical funnel situated at the industrial site of the thermal power station for different wind vectors and velocities. To simulate the heat exchange and aerodynamics near the funnel situated at the thermal power plant site we used the infrastructure that includes the following elements: mechanical compartment, substation, administrative building, warehouse and two cooling towers. The network model of the hydropower plant includes 1137782 units and 4741859 elements. A minimum orthogonal quality is 0.1 and a maximum biasing is 0.89. The ĝ RNG k– turbulence model, the Enhanced Wall Function and the Simplex algorithm were used for the velocity-pressure interrelation problem in steady flows. The air density is independent on the temperature at the computational volume inlet (the gravitation is neglected). The funnel surface temperature was specified as constant and equal to 100⁰ C. The heat exchange near the funnel was studied at different wind directions in the wind velocity range of 5 to 25 m/s. Hence, the wind direction, the environmental infrastructure and the industrial thermal power plant site have an essential effect on the funnel height heat exchange distribution pattern. Evidently, it is defined to a great extent by the funnel aerodynamics. A maximum heat loss level is observed when the flow is rushed to the backside of the building at the south- to-north wind direction and a minimum heat loss level is observed for the east- to -west and west -to -east wind directions for the parallel flow. А minimum heat loss is observed at a longitudinal wind motion along the mechanical compartment building in west-to-east and east-to- west directions. These specific features should be taken into account when designing tall funnels with an optimal change in the combustion product temperature along the funnel height. We can draw a conclusion that the specific features of the heat exchange in question should be obligatory taken into account when designing tall funnels. Keywords: heat exchange, funnel, thermal power plant infrastructure, mechanical compartment, wind direction and 3D model.
Heat exchange and aerodynamics of the vertical conical funnel at the thermal power plant site
Keywords: теплообмін; 3D-модель; димова труба; інфраструктура ТЕС; машзал; напрям вітру; heat exchange; 3D model; chimney; HPP infrastructure; mashzal; wind direction